Social Studies In The Postmodernism Era - Ida Bagus Weda Wigena,; Grystin D. Sumilat,; Arif Sobirin Wibowo, (Technium Social Sciences Journal, 2023)
Postmodernism is a new perspective on science and technology and today's social culture. The main feature of postmodernism is uncertainty. Humans today are in a condition filled with uncertainty, episodic and dynamic lifestyles. Changes in society occur very quickly, it is not uncommon for cultural shocks to occur, including in the world of education. The main goal of education is to humanize humans, so education must adapt to developments that occur locally to globally. Social studies education has a central role in dealing with the dynamics of social change. Postmodernism is one of the crucial challenges in social studies education learning. This study aims to 1) analyze the conditions and challenges of social studies education in the postmodern era and 2) analyze the fundamental skills that need to be taught in social studies education in the postmodern era. This research has a qualitative paradigm using library research. Data collection techniques for the study of related books, articles, and journals, using the hermeneutic data analysis method. Interpretive analysis shows that the emphasis on social studies learning is expected not only to focus on affective and cognitive aspects but also on life skills in the global era, which is synonymous with postmodernism. Adaptation skills, democracy, critical thinking, problem-solving, multiculturalism, socio-cultural relativism, and collaboration skills are needed to equip students to face the dynamics of postmodernism. Therefore, postmodernism in social studies education can be used as a philosophical foundation in the practice of compiling curriculum, materials, and the learning process of social studies education at every level of education.